﻿Ceriporiopsis tianshanensis (Polyporales, Agaricomycetes) and Sidera tianshanensis (Hymenochaetales, Agaricomycetes), two new species of wood-inhabiting fungi from Xinjiang, Northwest China - Tai-Min Xu; Yi-Fei Sun; Shun Liu; Chang-Ge Song; Neng Gao; Dong-Mei Wu; Bao-Kai Cui (MycoKeys, 2023)
Wood-inhabiting fungi are abundant in China, but their distribution is uneven, with more fungi in southwest China and fewer fungi in northwest China. During the investigation of wood-inhabiting fungi in Xinjiang, we collected a large number of specimens. Eight specimens growing on Picea schrenkiana were collected from Tianshan Mountains, and they were described as two new species in Ceriporiopsis and Sidera based on morphological characters and molecular evidence. Ceriporiopsis tianshanensis is characterized by a cream to salmon-buff pore surface, larger pores measuring 1–3 per mm, and broadly ellipsoid basidiospores 5–6.5 × 3–4 μm. Sidera tianshanensis is characterized by annual to perennial basidiocarps, measuring 15 mm thick, pores 5–7 per mm, cream to rosy buff pore surface, and allantoid basidiospores 3–3.5 × 1–1.4 µm. Detailed illustrations and descriptions of the novel species are provided.